Application of Surface Sound Speed Measurements in Post-processing for Multi-Sector Multibeam Echosounders - Beaudoin, J.D.; Clarke, J.E. Hughes; Bartlett, J.E. (The International Hydrographic Review, 2004)
Given sufficient data from ancillary sensors, swath sonar systems can generate sounding solutions in real time. The absolute accuracy o f these solutions depends both on the sonar-relative range and angle determination, and particularly on the quality of the aiding information. In this paper, we examine the correction of imperfect surface sound speed information for a multi-sector swath sonar. Difficulties arise from: (1) sector timings and boundaries changing with operational mode, and (2) insufficient information to determine the transmit sector associated with a receive beam. A number of post-processing strategies are proposed and the specific steps in implementation are described in detail.